The Role of Local Wisdom Values in Realizing the Concept of Building Planning and Environment in Gresik - Syaifuddin Zuhri; Imam Ghozali; Linggarkalbuadhi B. Lukito (Future Science, 2022)
Gresik has a wealth of architectural buildings as historical buildings that are very diverse and spread in almost all areas of the city because the potential of the historic building can be to strengthen local identity. On the other, currently the growth of urban buildings in the Gresik area still only prioritizes functional needs, especially commercial buildings or buildings that have economic potential, especially those located on the main roads of Gresik. The visual growth of these buildings does not take into account the values of local wisdom that can characterize the appearance of local buildings, and even now many are neglected and are not even a major consideration in the current city's visual design thinking. The symbolization of the city must of course be a guide in regulating the visual growth of the city, it can develop according to the architectural potential of the old city which can be expressed in the design of the building or environment. The author's thought in this study is how is the role of local wisdom values as a source of approach in regulating visual design guidelines for building layouts and the local environment, especially in commercial buildings which have been growing quite rapidly. The research uses the descriptive analysis method through observation and literature study in an effort to solve research problems that arise in the field. The preparation of the design process uses an iconic approach to get the visual characteristics of the city that are expressed in buildings. The visual potentials of the city originating from old buildings can be input in the design process and make these potentials as markers of a place or environment in an effort to create the characteristics of a place or environment.